COMPARISON OF DIETARY INTAKE WITH USDA MY PLATE GUIDELINES IN IN-PATIENTS SETUP AT TERTIARY CARE HOSPITAL OF LAHORE - Muhammad Jawad; Muteeba Komal; Faran Khan; Rubab Nadeem; Marriam Ahmed (International Journal of Pharmacy & Integrated Health Sciences, 2024)
Background: Poor dietary habits are linked to various risk factors, including obesity, hypertension, cardiovascular diseases, and diabetes. However, by making healthier nutritional choices, individuals can address these modifiable factors and significantly improve their overall health and well-being both now and in the future. Objectives: This study aimed to determine dietary intake among hospitalized patients and compare them with the standard dietary guidelines listed in USDA MyPlate. Methodology: The study sample was drawn using a simple random non-probability sampling technique. The 24-hour dietary recall method was implemented to find out the daily intake of food groups per day servings among the studied population. An independent sampling t-test with approximate standard deviation and p-value was performed to get the means of food groups. These mean intakes of food groups were compared according to standard guidelines by USDA MyPlate. Results: Hospital-related parameters have depicted that from total (n = 48) participants, 12.5% (n = 6) were underweight, 45.8% (n = 22) were normal, 37.5% (n = 18) were overweight and 4.2% (n = 2) were obese individuals. The average daily intake of protein servings was 1.66 for pediatric subjects. In comparison, the mean intake in the gynaecology, nephrology, cardiology, neurology, gastroenterology, medical unit, and ENT wards was 3.33, 1.33, 2.33, 3.00, 0.16, 0.50, and 0.00 servings, respectively, compared to the recommended 4.00 to 5.50 servings of protein. Conclusion: In conclusion, the intake of food groups was lowest for vegetables, followed by dairy products, fruit, and protein, and highest for grains when compared to USDA MyPlate.